Narratives of friendship and mental health - Doran, Dan (2022)
Research, theory and mental health policy draws attention to the importance of family, social networks, community, employers and learning contexts in maintaining mental health and inclusion. Yet the meaningful complexities of friendship to psychological health and public policy has not received sustained analysis, and policy emphasis is often restricted towards family relations.